Pengaruh Rotasi Pekerjaan dan Pengembangan Karir terhadap Motivasi Karyawan (Studi Kasus Pada Bank Panin Cabang Makassar) - Akhmad Muhammadin (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2022)
This study aims to test whether job rotation and career development can increase employee motivation at Panin Bank Makassar Branch. This type of research is a research using a quantitative approach. The sample used in this study totaling 71 employees using a simple random technique. Data collection method which is used is by distributing questionnaires. Data processing using multiple linear regression analysis with the help of SPSS 22 software for windows. The results of this study indicate that partially Job Rotation has no effect on Employee Motivation, Career Development has a positive and significant effect on Motivation Employees and simultaneous testing shows that, Job Rotation and Development Career positive and significant influence on Employee Motivation.